Effects Of Total Disc Replacement On Range Of Motion And Facet Stress In Lumbar Spine Using A Finite Element Analysis - Abd. Latif, Mohd Juzaila; Suarin, Mohd Azizan; Zakaria, Mohamad Shukri; Harun, Muhamad Noor; Nguyen, H.Q. (Penerbit UniMAP, 2021)
The focus of this study was to investigate the effects total disc replacement (TDR) on the range of motion (ROM) and facet joint stress at the lumbar spine region. A three- dimensional (3D) finite element model of the osseoligamentous lumbar spine was developed and subjected to the moment load in flexion, extension, left bending, and right torsion. The findings of this study indicated that the implanted spine with Prodisc-L caused an increase in ROM during flexion-extension motion and left bending motion ranged from 1% to 5%. However, ROM decreased during torsion motion by 7% after TDR. Meanwhile, the facet stress values increased at the treated level of L4L5 after Prodisc-L implantation ranging from 12% to 27% of diferences in all spine motion. But, decreasing values was observed in most of the adjacent level for both left and right facets. In brief, this phenomena could be one of the potential causes of early facet arthrosis, facet degeneration, and lower back pain in the immediate future.